DctR contributes to the virulence of avian pathogenic Escherichia coli through regulation of type III secretion system 2 expression - Yaodong Zhang; Yao Wang; Hong Zhu; Zhengfei Yi; Dossêh Jean Apôtre Afayibo; Chenglin Tao; Tao Li; Mingxing Tian; Jingjing Qi; Chan Ding; Shengqing Yu; Shaohui Wang (Veterinary Research, 2021)
Abstract Pathogens could precisely alter their gene expression to facilitate their survival and successful infection. The LuxR family transcriptional regulator DctR (also known as YhiF) was shown to participate in the regulation of acid fitness and adhesion of enterohemorrhagic E. coli (EHEC) O157:H7. Avian pathogenic Escherichia coli (APEC) causes significant economic losses to the poultry industries and also potentially threatens human health. However, the effects of DctR on the fitness and virulence of APEC have not been investigated yet. To assess the function of DctR in APEC, the dctR gene mutant and complemented strains were constructed and biologically characterized. Our results show that inactivation of the dctR gene led to decreased biofilm formation, diminished serum resistance, reduced adherence capacity, attenuated colonization and virulence of APEC in ducks. The altered capacities of the mutant strain were restored by genetic complementation. In addition, we found that DctR positively regulates the expression of E. coli type III secretion system 2 (ETT2) core genes in APEC. The expression of the inflammatory cytokines interleukin (IL)-1β and IL-8 were decreased in HD-11 macrophages infected with the mutant strain compared with the wild-type strain. These observations indicate that regulator DctR contributes to the virulence of APEC through regulation of ETT2 expression.